RELOCATION OF UKRAINIAN BUSINESS IN THE CONDITIONS OF WAR WITH RUSSIA - Kudyrko , L. P.; Obozny , V. V. (The actual problems of regional economy development, 2024)
The article examines the factors and trends of relocation of domestic companies to EU countries and other regions in connection with the deployment of active military operations on the territory of Ukraine. The purpose of the study is to analyze the peculiarities of the relocation of Ukrainian companies to EU countries in the context of the war with the Russian Federation. In the course of the research, both general scientific and special methods were used, including analysis and synthesis, elements of comparative analysis, empirical-statistical method, approaches of institutional analysis. Based on the generalization of modern works of domestic and foreign scientists, it is determined that in the practice of international business, processes of conflicting interaction of offshoring and reshoring strategies can be observed. This, in turn, changes approaches to the external relocation of national business under the influence of new factors, namely the activation of neo-protectionist slogans in the context of COVID-19 and the aggravation of geopolitical conflicts. It is noted that the factors of domestic business relocation are in most cases determined by the influence of military actions and their destructive consequences. Factors that encourage Ukrainian companies to relocate both within the country and abroad are considered. Analysis of the geospatial structure of domestic business movements showed that Ukrainian entrepreneurs mostly choose EU countries for foreign relocation. The advantages and risks faced by domestic business in a new environment have been identified. Familiarization with the case of the domestic company Ajax Systems, which chose Turkey as the location of its business, showed that an additional factor in favor of choosing a specific market is fiscal advantages and the availability of appropriate sectoral infrastructure for doing business. The theoretical significance of the research lies in the deepening of the theoretical understanding of the processes of globalization and international entrepreneurship in the modern era, as well as in obtaining additional knowledge about the mechanisms of strategic management in terms of factors influencing the international economic expansion of companies in the context of worsening geopolitical conflicts. The practical value of the study is related to determining the motivation of Ukrainian business when choosing specific relocation countries. Understanding the priority of the factors of the institutional environment based on the identification of the geographic structure of the choice of the foreign market can serve as a basis for increasing the efficiency of the regulatory system of modern Ukraine by branch. Prospects for further research are considered in the context of assessing the level and sources of competitiveness of Ukrainian enterprises in the new environment and the possibilities of implementing successful practices of their international business activities in the domestic regulatory and business environment.